THE FINANCIAL AND ECONOMIC ASPECT OF ASSESSING THE COMPETITIVENESS OF THE HOSPITALITY INDUSTRY - Baranova, Natalia; Bogatyreva, Liudmila (PEOPLE: International Journal of Social Sciences, 2018)
The paper considers traditional methods for assessing the competitiveness of the hospitality industry. The analysis of economic and financial indicators of some Russian hotels is carried out. An algorithm for assessing the competitiveness of enterprises in the hotel sector based on a statistical analysis of economic and financial indicators is proposed. The study allowed the authors to assess the competitiveness of the hotel enterprises. One of the factors of competitiveness of the hotel industry is the financial-economic situation, which may also be called a financially stable position, financial stability, and financial competitiveness.